2011
DOI: 10.1002/art.30159
|View full text |Cite
|
Sign up to set email alerts
|

Lung tissues in patients with systemic sclerosis have gene expression patterns unique to pulmonary fibrosis and pulmonary hypertension

Abstract: Objective. Pulmonary complications, including pulmonary fibrosis (PF) and pulmonary arterial hypertension (PAH), are the leading cause of mortality in patients with systemic sclerosis (SSc). The aim of this study was to compare the molecular fingerprint of lung tissue and matching primary fibroblasts from patients with SSc with that of lung tissue and fibroblasts from normal donors, patients with idiopathic pulmonary fibrosis (IPF), and patients with idiopathic pulmonary arterial hypertension (IPAH).Methods. L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

14
162
0
3

Year Published

2012
2012
2017
2017

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 195 publications
(179 citation statements)
references
References 40 publications
14
162
0
3
Order By: Relevance
“…Recent genomic studies using surgical biopsies from patients with IPF support these findings, and have, in addition, demonstrated pathological gene expression changes in processes such as coagulation, angiogenesis, inflammation, apoptosis, and regeneration (11)(12)(13)(14)(15). These studies revealed a number of possible pathological pathways, and helped to identify candidate biomarkers that could be used for early diagnosis, prognosis, and disease progression monitoring (16)(17)(18)(19)(20).…”
Section: Clinical Relevancementioning
confidence: 82%
“…Recent genomic studies using surgical biopsies from patients with IPF support these findings, and have, in addition, demonstrated pathological gene expression changes in processes such as coagulation, angiogenesis, inflammation, apoptosis, and regeneration (11)(12)(13)(14)(15). These studies revealed a number of possible pathological pathways, and helped to identify candidate biomarkers that could be used for early diagnosis, prognosis, and disease progression monitoring (16)(17)(18)(19)(20).…”
Section: Clinical Relevancementioning
confidence: 82%
“…Such unbiased approaches to gene expression analysis in PAH have been performed on peripheral blood mononuclear cells (12), whole lung tissue (13), and microdissected vessels (14). A recent study investigated proteomic changes in blood outgrowth ECs from four control subjects and four heritable patients with PAH (15) and another compared metabolomic and transcriptomic changes in PAECs engineered with a BMPR2 mutation (16), but no studies to date have specifically addressed changes in gene expression and the functional significance of those features in PAECs derived from patients with IPAH versus those from control lungs.…”
mentioning
confidence: 99%
“…Additionally, we and others have identified gene expression patterns that distinguish IPF from hypersensitivity pneumonitis, variants of disease that characterize distinct patterns of progression and characterize patients with pulmonary hypertension (9,(13)(14)(15)(16). A common limitation to all of these studies was the starting material used for analysis, since the IPF lung is known for its variable involvement and temporal heterogeneity (1).…”
mentioning
confidence: 99%